Effect of xylo-oligosaccharides on intestinal bacterial diversity in mice with spleen deficiency constipation - Ao, Xiang; Zhang, Zeying (Frontiers in Microbiology, 2024)
Objective: To explore the effect of xylo-oligosaccharides on intestinal bacterial diversity in mice with spleen deficiency constipation.Method: The 16S rDNA sequencing was used to identify microbiota composition in four groups, including the normal group (NG), the model group with spleen-deficiency constipation (SDC), XOS treated groups that include XOS1 groups treated XOS 0.05g/mL•d, and XOS2 group treated XOS 0.1g/mL•d. Chao1 and Shannon were used to conduct gut microbes diversity analysis. Linear discriminant analysis coupled with effect size measurements (LEfSe) was used to identify signature gut microbiota, and phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) was used to predict the function of altered gut microbiota.Results: Veen map indicated 245 common OTUs were identified from four groups.Especially, 9, 3, 0, and 19 unique OTUs were identified in NG, SDC, XOS1 and XOS2 groups, respectively. The shannon index was evidently higher in NG group than in the other three groups (P<0.05). We identified the occurrence of dominant bacterial groups including Bacteroidetes (25.5 49.9%), Firmicutes (25.4 39.3%), Proteobacteria (12.5 24.9%), Deferribacteres (1.6 19.2%), Cyanobacteria (0.3 1.8%), Verrucomicrobia (0.02 1.6%), Actinobacteria (0.01 0.5%) and Tenericutes (0.03 0.09%) at the four groups. The XOS2 group was characterized by a higher abundance of peptostreptococcaceaePeptostreptococcaceae, intestinibacterIntestinibacter, aerococcaceaeAerococcaceae, and facklamiaFacklamia. XOS1 group enriched in deferribacteresDeferribacteres, mucispirillumMucispirillum, deferribacteralesDeferribacterales, deferribacteresDeferribacteres, lachnoclostridiumLachnoclostridium, rhodospirillaceae Rhodospirillaceae and rhodospirillalesRhodospirillales. Meanwhile, the SDC mice showed dramatic enrichment in rikenellaceaeRikenellaceae, lachnospiraceaeLachnospiraceae, rikenellaceaeRikenellaceae, roseburia Roseburia and alistipesAlistipes, which were highly abundant in the NG group. XOS fed-mice evidently increase deferribcteres Deferribcteres abundance compared with NG and SDC groups. However, the abundance of Rikenellaceae was significantly reduced in XOS1 and XOS2 groups compared with NG and SDC groups. We identified that altered gut microbiotas by XOS treatment were associated with various metabolic pathways, including organismal systems, metabolism, human diseases, genetic information processing, and cellular processes. Conclusion: Our research indicated that XOS has the potential to recover intestinal bacteria and contribute to the treatment of spleen deficiency constipation.